Genesis - Alter, Robert (New York : W.W. Norton, 1996)
Genesis begins with the making of heaven and earth and all life, and ends with the image of a mummy - Joseph's - in a coffin. In between come many of the primal stories in Western culture: Adam and Eve's expulsion from the garden of Eden, Cain's murder of Abel, Noah and the Flood, the destruction of Sodom and Gomorrah, Abraham's binding of Isaac, the covenant of God and Abraham, Isaac's blessing of Jacob in place of Esau, the saga of Joseph and his brothers. These are stories we attend to throughout our lives, for their literary power and beauty, their emotional resonance, their philosophical weight, and their sacredness. They connect us with one another and with generations past and future.
In Robert Alter's brilliant translation, these stories cohere in a powerful narrative of the tortuous relations between fathers and sons, husbands and wives, elder and younger brothers, God and his chosen people, the people of Israel and their neighbors. Alter's translation recovers the meanings, literary strategies, and eloquence of the ancient Hebrew and conveys them in striking literary English. The result is a Genesis with the continuity of theme and motif of a wholly conceived and fully realized book. Alter's translation is enhanced by his insightful, fully informed commentary, which illuminates the book in its many dimensions.
Includes bibliographical references (p. 307-308) and index.
Keywords: Bible. -- Commentaries; Bible -- Commentaries; Genesis (bijbelboek); Genesis; Kommentar